The consequences of key audit matters on users: The case of Spain - Ascenso, T. (2021)
The audit report has changed by adding a section to disclosure the key audit matters (KAM), among other changes. The KAM disclosure may have incremental investor’s usefulness. Thus, we study the influence of the KAM disclosure on investor usefulness using a short window and a year window market reaction, this is, a return and cumulative abnormal return model (CAR). Since most of the disclosure KAM studies are in a strong investor protection and common law system countries, we study the influence of the KAM disclosure in Spain. In Spain the audit report changes is mandatory for periods beginning on or after 17 June 2016. We find a one year market reaction and that the KAM disclosure is value relevant for investors, but not in a short market reaction to KAM disclosure. Albeit, finding a one year reaction, our findings are similar to the archival studies, which have found no market reaction to KAM disclosure. This may be due to the fact the information disclosure by KAM is already known by investors.